Bax/Tubulin/Epithelial-Mesenchymal Pathways Determine the Efficacy of Silybin Analog HM015k in Colorectal Cancer Cell Growth and Metastasis - Amawi, Haneen; Hussein, Noor A.; Ashby, Charles R.; Alnafisah, Rawan; Sanglard, Leticia M.; Manivannan, Elangovan; Karthikeyan, Chandrabose; Trivedi, Piyush; Eisenmann, Kathryn M.; Robey, Robert W.; Tiwari, Amit K. (Frontiers in Pharmacology, 2018)
The inhibition of apoptosis, disruption of cellular microtubule dynamics, and over-activation of the epithelial mesenchymal transition (EMT), are involved in the progression, metastasis, and resistance of colorectal cancer (CRC). Therefore, the design of a molecule that can target these pathways together is a very effective strategy to reverse CRC progression and metastasis. In this study, twelve novel silybin derivatives, HM015a-HM015k (15a-15k) and compound 17, were screened for their cytotoxicity in CRC cell lines. Compounds HM015j and HM015k (15k and 15j) significantly decreased cell proliferation, inhibited colony formation, and produced cell cycle arrest in CRC cells. Furthermore, 15k significantly induced the formation of reactive oxygen species and apoptosis. It induced the cleavage of the intrinsic apoptotic protein (Bax p21) to its more efficacious fragment, p18. Compound 15k also inhibited tubulin expression and disrupted its structure. Compound 15k significantly decreased metastatic LOVO cell migration and invasion. Furthermore, 15k reversed mesenchymal morphology in HCT116 and LOVO cells. Additionally, 15k significantly inhibited the expression of the mesenchymal marker N-cadherin and upregulated the expression of the epithelial marker, E-cadherin. Compound 15k also inhibited the expression of key proteins known to induce EMT (i.e. DVL3, β-catenin, c-Myc) and upregulated the anti-metastatic protein, cyclin B1. Overall, 15k significantly inhibited CRC progression and metastasis by inhibiting apoptosis, tubulin activity and the EMT pathways. Overall, these data suggest that compound 15k should be tested in vivo in CRC animal model for further development.